Ethical Education in the Perspective of Imam Az-Zarnuji - Suwanto, Suwanto; Lubis, Anisah Sari; Hanum, Azizah (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2024)
This study explores the views of Imam Az-Zarnuji on ethical education, as outlined in his classical work,